Current perspectives on attachment and bonding in the dog–human dyad - Payne, Elyssa (Psychol Res Behav Manag, 2015)
This article reviews recent research concerning dog–human relationships and how attributes that arise from them can be measured. It highlights the influence of human characteristics on dog behavior, and consequently, the dog–human bond. Of particular importance are the influences of human attitudes and personality. These themes have received surprisingly little attention from researchers. Identifying human attributes that contribute to successful dog–human relationships could assist in the development of a behavioral template to ensure dyadic potential is optimized. Additionally, this article reveals how dyadic functionality and working performance may not necessarily be mutually inclusive. Potential underpinnings of various dog–human relationships and how these may influence dogs’ perceptions of their handlers are also discussed. The article considers attachment bonds between humans and dogs, how these may potentially clash with or complement each other, and the effects of different bonds on the dog–human dyad as a whole. We review existing tools designed to measure the dog–human bond and offer potential refinements to improve their accuracy. Positive attitudes and affiliative interactions seem to contribute to the enhanced well-being of both species, as reflected in resultant physiological changes. Thus, promoting positive dog–human relationships would capitalize on these benefits, thereby improving animal welfare. Finally, this article proposes future research directions that may assist in disambiguating what constitutes successful bonding between dogs and the humans in their lives.